On the impact nature of the Ilyinets annular structure according to gravity gradients - Dubovenko, Yu.І.; Chorna, О.А. (Reports of the National Academy of Sciences of Ukraine, 2022)
The materials of the geological structure and geophysical study of the Ilyinets annular structure on the southwestern slope of the Ukrainian Shield are generalized and supplemented. The structure of the central part of the crater is modeled according to the data of the joint analysis of 2D and 3D models of the gravity field and its transformants — modules of the gravity horizontal gradient. Because of modeling, the periodic wavy nature of the destruction of the host rocks in the center of the structure was revealed. According to the analytical continuation of the observed gravity field upward on 1 km above the center of the crater the destruction front is delineated. These results can be interpreted in favor of the additional confirmation of the impact hypothesis regarding the genesis of the Ilyinets structure. From the standpoint of the wave process, the approximate parameters of the impact event are estimated — the mass of the meteoroid, the depth of penetration, and the energy of the explosion. These estimates deviate by more than 5 % from the data known from the literature. Estimate 2. 57 · 1025 erg is intended for the energy range for medium-scale impact events.